Pasture-Based Swine Management: Behaviour and Performances of Growing-Finishing Pigs - Riccardo Fortina; Alberto Brugiapaglia; Sonia Tassone; Vanda Malfatto; Andrea Cavallero (Scientific Papers Animal Science and Biotechnologies, 2023)
A pasture-based swine management (PBSM) trial was conducted in Piemonte (N-W Italy) to study the performances and the carcass yield of 16 hybrid pigs (8 castrated males and 8 females; average initial weight: 90 kg). Animals were allowed to forage pea, clover, beet and alfalfa pastures for 170 days in a crop-pasture rotation on different paddocks. A concentrate was fed to supply 50% of estimated energy requirements. Forage dry matter intake (DMI) ranged from 0.32 kg/day (alfalfa) to 2.85 kg/day (pea), depending on the period and forage type. Pigs were weighted every 30 days and at slaughtering; average daily gain (ADG) was 0.29 kg. The stocking rate (SR) ranged from 109 kg/ha LW (clover) to 2347 kg/ha LW (pea). Data collected at slaughtering (average final weight: 141 kg) were: hot carcass weight and yield, lean and fat cuts weight, backfat thickness, pH45 and pH24. The statistical analysis (ANOVA of SPSS) did not show differences between males and females. Results showed that PBSM should be especially appealing to limited-resource farmers due to low inputs needed; pasture can be used to replace 50% of the nutritional needs, helping to save on grain costs, without affecting carcass characteristics.